Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perbankan - Redhona Gevi Waluyo Putri; Setiawati, Erma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of Good Corporate Governance on financial performance in conventional banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The method used is quantitative with a secondary data approach obtained from annual financial reports. The sample was determined through a purposive sampling technique with certain criteria, and data analysis was carried out using multiple linear regression with the help of SPSS software. The independent variables in this study include the independent board of commissioners, company size, audit committee, and institutional ownership, while financial performance is the dependent variable measured by the capital adequacy ratio. Before the regression test was carried out, the data was first tested using the classical assumption test, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results showed that the independent board of commissioners and company size did not have a significant effect on financial performance, so that hypotheses H1 and H2 were rejected. Meanwhile, the audit committee has a significant effect on financial performance so that hypothesis H3 is accepted, while institutional ownership shows a significant effect but the direction of the relationship is not as expected, so hypothesis H4 is still rejected.